Sistem Proses Validasi Pada Pembinaan Karir Prajurit Militer Dengan Metode Rule-Based Reasoning Berbasis User Centered Design (Studi Kasus: Jajaran Korem 163) - Putra, I Putu Gede Maysa; Raharja, Made Agung; Wibawa, I Gede Arta; Putra, I Gusti Ngurah Anom Cahyadi (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 13 No 2 (2024): JELIKU Volume 13 No 2, November 2024, 2025)
In the digital era, many organizations, including Korem 163, are adopting digital systems to enhance administrative efficiency. This study addresses the challenges of career development data validation at Korem 163 using a rule-based reasoning method, which automates data checks and reduces human error. This system ensures accurate data for fair promotion decisions and utilizes User-Centered Design (UCD) according to ISO standards to enhance usability. Blackbox Testing results show optimal performance with all scenarios passing, maintaining data integrity and demonstrating high reliability. Further implementation and regular monitoring are recommended. The system achieved 100% accuracy in personnel selection and received a System Usability Scale (SUS) score of 84.29, placing it in the Good Usability category with a grade B. Qualitative evaluation rated the system as Excellent, confirming its ease of use and efficiency, making it highly suitable for practical use and providing valuable insights for personnel management in military organizations.